Managing Change in Organizations : develop your employees for business transformation - Grigsby, Mike (London: New York, NY: Kogan Page, 2023)
"You don't have to be a change manager to be managing change. Written for managers, HR and OD professionals, this practical guide tells you everything you need to know to support effective business transformation. Managing Organizational Change provides practical tools, tips and examples on how to manage the people side of change as well as advice on how to engage staff and support them during times of business flux and uncertainty. There is also expert advice on how to ensure that all change activity in the company is aligned with the overall business goals whether this affects people, practices or processes.. There is also expert guidance for HR, OD and management professionals on how to manage staff expectations, communicate change effectively and prioritise wellbeing during times of change. It includes practical tools which explain how to develop everyday activities to support the workforce through noticing, checking-in and navigating. Supported by case studies from both private and public sector organizations including Virgin Media, Close Brothers, Oxfam, NHS and the UK Civil Service, this book is crucial reading for all HR and OD professionals as well as line managers needing to manage change in their organizations"--
Includes bibliographical references and index.
Keywords: Organizational change -- Management; Organizational behavior